Attitude, Support of Husband, and Exclusive Breast Feeding in Working Area of Jembatan Kecil Public Health Center Bengkulu - Yulita Elvira Silviani; Ayu Amalia Pranciska (Jurnal Sains Kesehatan, 2018)
Exclusive breastfeeding is breastfeeding without giving other foods or drinks immediately after birth until the age of 6 months. Exclusive breastfeeding for 6 months is recommended by international guidelines based on scientific evidence about the benefits of breastfeeding for infants, mothers, families and countries. This study aims to study the relationship of maternal attitudes and husband's support with exclusive breastfeeding in the work area of Jembatan Kecil Puskesmas in Bengkulu City. This study uses descriptive correlational method, with cross sectional design. The population in this study were all mothers who had babies aged 6 months who were in the working area of the Jembatan Kecil Health Center in Bengkulu City, which were 193 people. The technique in this study uses accidental sampling and obtained a sample of 66 samples. Collecting data in this study uses a questionnaire by distributing and filling questionnaires. The analysis used was univariate and bivariate. The results of the study were obtained: (1) out of 66 samples in the working area of the Jembatan Kecil Public Health Center in Bengkulu City there were 35 people (53.0%) not giving exclusive breastfeeding. (2) out of 66 samples in the working area of the Jembatan Kecil Public Health Center in Bengkulu City, there were 29 people (43.9%) negative attitudes in exclusive breastfeeding. (3) out of 66 samples in the working area of the Jembatan Kecil Public Health Center in Bengkulu City there were 23 people (34.8%) husbands who did not support exclusive breastfeeding. (4) There is a significant relationship between the attitudes of mothers with exclusive breastfeeding in the working area of the Jembatan Kecil Health Center in Bengkulu City, with a moderate relationship category. (5) There is a significant relationship between the husband's support and exclusive breastfeeding in the working area of the Jembatan Kecil Health Center in Bengkulu City, with a moderate relationship category. To further enhance the provision of information about exclusive breastfeeding through health promotion, health education and counseling that not only involves mothers but also includes husbands as motivators in the practice of exclusive breastfeeding and control of other factors such as mass media, socio-cultural so as not to affect mothers. Keywords: exclusive breastfeeding, mother's attitude, husband's support